Roving residency : Nikhil Chopra. - Chopra, Nikhil (University of Melbourne, VIC : Asialink, 2013)
"In 2012 interdisciplinary artist Nikhil Chopra became the inaugural recipient of Asialink's 'Roving Residency' which unfolded across three Australian locations: Carriageworks, Sydney; Asialink, Melbourne; and the Fremantle Arts Centre, Western Australia. Chopra's Roving Residency launched Asialink's new 'Arts Residency Laboratory', a platform through which new, more sustainable and engaged models of arts residencies are trialled in the context of the Asian Century"--Introduction.
Cover title.
Keywords: Chopra, Nikhil -- Exhibitions; Installations (Art) -- 21st century -- Australia -- Exhibitions; Australian